Plagiarisme Modul Pembelajaran Teori Kunci Enormas College Perspektif Fatwa MUI Nomor 1 Tahun 2005 Tentang Perlindungan HaKI: Analisis Sengketa Antara PT. Delta Edukasi Semesta dan PT. ENS Indonesia - Muhammad Rafi Akbar; Annisa Sativa (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The case of learning module plagiarism between PT. Delta Edukasi Semesta and PT. ENS Indonesia raises important issues related to the protection of Intellectual Property Rights (IPR) and ethics in the use of copyrighted works. This research aims to analyze this case based on a normative juridical perspective by referring to Law no. 28 of 2014 concerning Copyright, as well as a moral review of the Fatwa of the Indonesian Ulema Council (MUI) Number 1 of 2005 concerning Copyright. The research method used is descriptive qualitative, by collecting data through literature studies which include statutory regulations, scientific literature and related decisions. The research results show that PT Delta Edukasi Semesta has the potential to violate PT. ENS Indonesia copyright if it is proven to have copied, used or distributed the module without permission. From a legal point of view, this action can be subject to sanctions according to Law no. 28 of 2014, while from a moral perspective, acts of plagiarism are also considered haram according to the MUI Fatwa because they violate the principles of justice in Islam. Thus, this case emphasizes the importance of legal and moral protection for intellectual work, especially in the field of education.